ASSESSMENT OF GROUNDWATER CONTAMINATION BY PETROLEUM PRODUCTS IN BARUWA COMMUNITY LAGOS, NIGERIA (2017)
Contamination of petroleum products in groundwater in Baruwa community, Lagos has been widely reported, as a result of ageing pipelines and vandalisation. Information on the types, nature of hydrocarbon and other contaminants that could assist in assessing the level of contamination is lacking. This study was therefore designed to assess the hydrogeochemical settings (delineate aquiferous units, quantify contaminated unit and define types of hydrocarbon present) in the groundwater resources of Baruwa community, Lagos state Nigeria. The study was also carried out to estimate areas that require remediation in the groundwater resources. Based on preliminary studies, two boreholes (depth 36-42 m), one each in uncontaminated and contaminated areas were drilled to determine hydrogeological sequences in the Baruwa community. Twenty four sediment samples from the drilled boreholes were purposively selected for sedimentological analysis and determination of some hydraulic properties using standard methods. Thirty groundwater samples were collected purposively from the two drilled and other available boreholes and were analysed for heavy metals, cation / anions and the hydrocarbon content using Atomic Absorption Spectrophotometric, Colorimetric and Gas Chromatography- Mass Spectrometric methods, respectively. Data were compared with the WHO standards for potable water. Various thematic maps were developed using appropriate software. The area of contaminated land and volume of water that would require remediation were estimated hydrogeologically from the thematic maps. Three aquifer units were identified at depths 9.0, 21.0 and 30.0 m. Aquifer grain size graphic mean was 1.64 indicative of medium to coarse grained moderately sorted leptokurtic sands. These were suggestive of materials deposited under low energy condition in a fluvial or tidal environment. The porosity ranged from 15.9 to 19.9%. The permeability coefficients of the aquifer were 9.469 x 10-5, 4.105 x 10-5 and 5.102 x 10-5 mm/sec, respectively. The range of total hardness and pH were 2.6-248.6 mg/L and 4.4-6.7. Heavy metals, cations and anions concentration (in mg/L) in the groundwater samples ranged from 0.0-0.4 (Zn), 0.1-1.6 (Mn), 0.1-2.6 (Fe), 0.4-77.8 (Mg2+), 0.25-13.20 (Ca2+), 24.5-286.3(Cl-), 0.1-1.2 (NO3 -), 1.4- 88.2(SO4 2), 0.0-0.2(PO4 3-), Lead, chromium, cadmium, nickel were below the detection limits. The samples from the contaminated area revealed enhanced concentrations of hydrocarbon, metals and anions when compared with the uncontaminated borehole samples. Data fall within the WHO limits except for Fe and Mn. Compounds identified were C20H34O8, C27H56, C21H44, C24H50, C21H34O3 indicating heavy oils. The estimated area in need of remediation was 9.9 million metre square with an approximate volume of 89.1 million cubic meter of water. Groundwater contaminants in Baruwa community were mainly heavy oils and heavy metals. The area of contaminated land that needs remediation has been calculated and volume of water that needed remediation had also been determined. Keywords: Aquiferous units, Sedimentological analysis, Groundwater Contamination, Hydraulic properties Word count: 428